Prevalence and incidence of upper-limb work-related musculoskeletal disorders at repetitive task workstations in a dairy factory - Raposo, A (2017)
Work-related musculoskeletal disorders (WMSDs) are a leading work-related health issue. Work-related disability and illness are common in a wide range of activities. The association of the musculoskeletal disorders and work possibly have a temporal cause-effect relation. This study investigated the prevalence and incidence of upper-limb work-related musculoskeletal disorders in a factory dairy products. The study was carried out between 2010 and 2014 among the 166 workers belonging to the cheese sector. Two evaluations were done, one in 2011 and another in 2014 and the study is limited to a total of 134 workers who were evaluated in both. It was found a total symptoms prevalence of upper limb musculoskeletal disorders of 38.1% and 31,1% in the first and second evaluation, respectively. Respect to the incidence of musculoskeletal disorders from the first to the second evaluation, the value found was 8.2% These values justifies the need to undertake preventive measures, reducing the injuries and consequently costs associated with these disorders. (c) 2017 Taylor & Francis Group, London.